ANALISIS FAKTOR-FAKTOR PENENTU KEBERHASILAN DALAM IMPLEMENTASI ENTERPRISE RESOURCE PLANNING PADA PT. PERTAMINA PATRA NIAGA - Andy Prihatmoko (Universitas Insan Pembangunan Indonesia, 2019)
Abstract PT. Pertamina Patra Niaga as one of the subsidiaries of PT. Pertamina (Persero) has been using Enterprise Resource Planning (ERP) system products with SAP (Systems, Applications and Products in Data Processing) since 2010. The full life cycle implementation of SAP took a long time and produced back logs. In 2014 the SAP was enhanced to be MySAP appropriate with its business development. Therefore, PT. Pertamina Patra Niaga should understand the critical success factors for the implementation of enhanced MySAP. This study aimed to examine the critical success factors in ERP implementation at PT. Pertamina Patra Niaga. The use of factor variables based on the results of previous studies that found direct influences of Top Management Support, Effective Project Management, Business Process Reengineering, Education and Training, Vendor Support and Organization Culture on the success of ERP implementation. The research tool was questionnaires distributed to the parties that had an interest in ERP implementation. The analytical method was chosen by Structural Equation Modeling (SEM) which with AMOS (Analysis of Moment Structure) software. The results of this study indicate that the Top Management Support, Effective Project Management, Business Process Reengineering and Education and Training have positive and significant impact on the success of the ERP system implementation at PT. Pertamina Patra Niaga. Keywords : Critical Success Factor, CSF, Enterprise Resource Planning, ERP, ERP implementation